Carnivorous mushrooms : lassoing their prey? - Gentle, Victor (Milwaukee, Wis. : Gareth Stevens Publishing, 1996)
This book introduces some varieties of fungi that eat eelworms, describing the damage these tiny worms cause to both plants and animals and the different ways that the fungi trap their prey.
Includes index.
Includes glossary.
Includes bibliography.
4-8
Keywords: Fungi; Carnivorous plants